PERAN GURU PAI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA DI SEKOLAH UMUM - Rasi Maya Sari; Mahfus Mahfus; Deri Wanto (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2020)
The present study aimed at finding out a depiction of PAI teacher’s role in improving students' ability to read the Qur'an in a public school, namely SDN 14 Lebong, Bengkulu. Resting upon the focus intended, the answers were found through research. Thus, a qualitative approach was employed with the subjects studied referring to fifth grade students, and the informants were PAI teacher as well as the school principal. The data were garnered from interview and observation techniques, so the following conclusion was found: the role that had been carried out by the PAI teacher was very helpful for students in learning to read the Qur'an. PAI teacher succeeded in helping students from the condition that they did not understand or even did not know any of hijayyah letters to the condition that they understood and began to recognize hijayyah letters. It was in so doing although some obstacles were found both from students’ internal case and from school facilities.Keywords: Teacher’s Role, Ability to read the Qur'an